Understanding and identifying musical intervals: a comprehensive K-12 curriculum - Reist, Thad (My University, 2025)
This report presents lessons from a curriculum designed to introduce the concept of musical intervals to lower elementary students, and to continue the understanding of musical intervals as students move upward by grade from K-12. I have both expanded upon others’ games and activities and invented my own games and activities to teach the concept of intervals using music classroom materials such as buckets, boomwackers and instruments, xylophones and piano. I have composed short pieces and exercises to demonstrate intervals to all grades. This curriculum begins at the kindergarten level, when students are introduced to the concepts of two pitches being the same, different, higher, and lower. By the 12th grade, students will be able to identify all intervals between the unison and octave. I believe the recognition of intervals is beneficial to becoming a well-rounded musician and is one of the initial vital steps to unlocking musical potential. Consequently, many students learned musical intervals and were able to identify them in the music they were learning. During my Masters’ studies, I was exposed to multiple music education philosophies and theories of music teaching, all of which were new to me. I do not have a bachelor’s degree in education, and during my first year of teaching I knew that I needed to acquire more knowledge to be a successful music educator. In learning music education philosophies, what resonated the most for me was Christopher Small’s assertion that music is ultimately about relationships of many types. In my Organization and Administration of School Music Programs course, the overarching theme was also about relationships. This was of vital importance to my development as an educator because I have been building a music program in my district from the ground up. Crucial to this is the relationships that I, the sole music teacher, develop and nurture with students, their parents and the community. Furthermore, bringing people together for musicking, with the goal of producing better people and societies, is important to me. In creating these lessons about musical intervals, my challenge was to build trust and make this activity fun for students. Students are naturally competitive, turning the learning of intervals into a game is a way to do so. In my goal to build a successful music program from K-12, learning foundational concepts such as intervals is critical to ear training, sight reading and playing, composition, and improvisation.
Keywords: Music education; K-12; Musical intervals; Ear training